Impact of Ultrasound Cycloplasty on Intraocular Pressure and Clinical Outcomes in Angle-Closure Glaucoma: A Systematic Review and Meta Analysis - Putra, Hisyam Hartaman; Djumain, Rahmadina; Satria, Dafi Irsan; Muhammad, Aan Tri Lutfi; Mahendra, Brian Arditya (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
Introduction: Angle-closure glaucoma (ACG) is a leading cause of permanent blindness, especially in Asia. Conventional therapies often fail to provide long-term intraocular pressure (IOP) control. Ultrasound Cycloplasty (UCP), a high-intensity focused ultrasound (HIFU) technology, lowers IOP through selective coagulation of the ciliary processes. This review aimed to evaluate the effectiveness and safety of UCP in patients with ACG. Methods: A literature search was conducted in PubMed, Scopus, and Wiley until October 2025. Inclusion studies included ACG patients undergoing UCP with reported IOP outcomes, antiglaucoma medication use, and complications. Meta-analysis used a random-effects model and sensitivity analysis with a fixed-effects model. Results: Four studies involving 142 eyes were analyzed. UCP reduced IOP by 18.12 mmHg, though not statistically significant (95% CI –1.27 to 37.51) with very high heterogeneity (I² = 99%). Antiglaucoma medication use decreased significantly (MD 1.79; p = 0.02). Early/mild complications were more common than late/severe complications. Sensitivity analysis showed stable results with reduced heterogeneity. Conclusion: UCP is potentially effective in reducing IOP and antiglaucoma medication use in ACG patients, with an acceptable safety profile. However, considerable inter-study variability suggests that prospective studies are needed.